2009
DOI: 10.3923/pjbs.2009.473.475
|View full text |Cite
|
Sign up to set email alerts
|

A New Index for Discrimination Between Iron Deficiency Anemia and Beta-Thalassemia Minor: Results in 284 Patients

Abstract: The present study reports the results in 284 patients of applying a recently developed index, MCV-(10 x RBC), for discrimination between beta-thalassemia trait (beta-TT) and Iron Deficiency Anemia (IDA), the two most common causes of microcytic hypochromic anemias. A total of 284 carefully selected patients (130 patients with IDA and 154 with beta-TT) were studied. Sensitivity, specificity and Youden's index were compared between the proposed index and four other indices, namely England-Fraser, Mentzer, Srivas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 15 publications
6
43
2
Order By: Relevance
“…In their study, the Mentzer and Ehsani et al indices were able to correctly diagnose 94.7% and 92.9% of cases, respectively, and both are easy to calculate [11]. Similar results (Mentzer index: sensitivity, 90.9%; specificity, 80.3%) were found by Ghafouri et al [19].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In their study, the Mentzer and Ehsani et al indices were able to correctly diagnose 94.7% and 92.9% of cases, respectively, and both are easy to calculate [11]. Similar results (Mentzer index: sensitivity, 90.9%; specificity, 80.3%) were found by Ghafouri et al [19].…”
Section: Discussionsupporting
confidence: 62%
“…The differential values for each discrimination index were applied as defined in the original published reports: red blood distribution width index (RDWI), Mentzer index [4], the Shine and Lal index [5], the England and Fraser index [6], the Srivastava index [7], the Green and King index [8], the Ricerca et al index [9], and the Sirdah et al index [10]. The Ehsani et al index [11], mean density of hemoglobin per liter of blood (MDHL), mean cell hemoglobin density (MCHD) [12], and RBC count were evaluated and compared. The values of each index required to distinguish between β -TT and IDA and the number and proportion of correctly identified patients (true positives) calculated using these indices are shown in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Ehsani et al showed that the best discrimination index according to Youden's criteria was the Mentzer index (90.1%), followed by the Ehsani et al index (85.5%). In their study, the Mentzer and Ehsani et al were able to correctly diagnose 94.7% and 92.9% of cases, respectively [12]. Similar results (Mentzer index: sensitivity, 90.9%; specificity, 80.3%) were found by Ghafouri et al [13].…”
Section: Discussionsupporting
confidence: 73%
“…The purpose of using indices to discriminate anemia is to detect subjects who have a high probability of requiring appropriate follow-up and to reduce unnecessary investigative costs. Since 1970, a number of complete blood count indices have been proposed as simple and inexpensive tools to determine whether a blood sample is more suggestive of -TT or IDA [12,[18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to simplify the differential diagnosis between IDA and TT, several indices using blood cell count parameters have been suggested 9, 10, 11, 12, 13, 14, 15, 16. The formula developed by Green & King {[(MCV 2 ) × RDW]/(Hb × 100) where MCV is mean corpuscular volume, RDW is RBC distribution width and Hb is hemoglobin} has, according to many studies, a good performance 16, 17, 18.…”
Section: Introductionmentioning
confidence: 99%